Findings of social gender inequality in counseling process - (:unkn) unknown (Sakarya University, 2016)
The general aim of the research is to identify the context of social gender inequality (SGI) encountered by psychologists and psychological counselors during the course of counselling, reveal their approaches, their opinions and perceptions about these contexts and bring into discussion their counselling approach considering SGI. The research is designed based on a phenomenological pattern, which is a qualitative research pattern. The study group consist of 10 psychologists and 8 psychological counselors, 8 males and 10 females from 8 different cities. The results of the study show that participants believe existence of SGI in Turkey and encounter SGI during the course of counselling. The greater part of the cases are female clients. The most preferred methods are creating awareness and insight about SGI. Solution Focused Brief Therapy and then Cognitive Behavioral Therapy are the most commonlyused approaches. The proper counseling environment is defined as to where the counselee feels free to explain her/himself truly comfortably. The participants recommend an environment that is purified from any material which can evoke SGI. They believe that the solution of the SGI depends on increasing the level of education. © The Turkish Online Journal of Educational Technology.